2017
DOI: 10.1016/j.lwt.2017.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of an anthocyanin-rich blackberry (Rubus spp.) by-product extract by freeze-drying

Abstract: One approach to improving sustainable food production is to add value to fruit by-products, which are currently used as animal feed or discarded, yet may be useful sources of natural antioxidants due to their phenolic compounds. Hence, the present work aimed to produce and evaluate two products prepared from an anthocyanin-rich extract of a blackberry by-product through freeze-drying. Maltodextrins with 10 and 20 dextrose equivalent (DE), were assessed as the carrier matrices. The maltodextrin DE did not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(108 citation statements)
references
References 44 publications
6
81
0
13
Order By: Relevance
“…colorants, emulsifiers, thickeners, antioxidants, among others) (Azeredo, 2009;Dias et al, 2016;Gong and Bassi, 2016). Although numerous methodologies can be found in literature for bioactive compounds recovery like ultrafiltration, supercritical fluid extraction, ultrasound extraction, resin adsorption, encapsulation and spray drying among others (da Silva et al, 2016;Destro dos Santos et al, 2016;Kaderides and Goula, 2017;Li et al, 2012;Medina-Meza and Barbosa-Cánovas, 2015;Yamashita et al, 2017), five distinct recovery stages can principally be observed: macroscopic pre-treatment, macro and micromolecules separation, extraction, purification and nutraceuticals formation (Galanakis, 2012).…”
Section: Peak Tentative Identificationmentioning
confidence: 99%
“…colorants, emulsifiers, thickeners, antioxidants, among others) (Azeredo, 2009;Dias et al, 2016;Gong and Bassi, 2016). Although numerous methodologies can be found in literature for bioactive compounds recovery like ultrafiltration, supercritical fluid extraction, ultrasound extraction, resin adsorption, encapsulation and spray drying among others (da Silva et al, 2016;Destro dos Santos et al, 2016;Kaderides and Goula, 2017;Li et al, 2012;Medina-Meza and Barbosa-Cánovas, 2015;Yamashita et al, 2017), five distinct recovery stages can principally be observed: macroscopic pre-treatment, macro and micromolecules separation, extraction, purification and nutraceuticals formation (Galanakis, 2012).…”
Section: Peak Tentative Identificationmentioning
confidence: 99%
“…Fleshy fruit acidity is mainly caused by the organic acids present in most ripe fruits (Etienne, Génard, Lobit, Mbeguié-A-Mbéguié, & Bugaud, 2013). Yamashita et al (2017) also showed that products obtained after the lyophilisation of blackberries caused high acidity.…”
Section: Ph Value Of Batter With Different Amounts Of Freeze-dried Blmentioning
confidence: 95%
“…Blackberries are a great source of anthocyanin pigments (Fan-Chiang & Wrolstad, 2006), and the content of these pigments plays a critical role in determining the colour quality of many fresh and processed fruits (Giusti & Wrolstad, 2005). For example, an anthocyanin-rich extract of a blackberry by-product was obtained through freeze-drying (Yamashita et al, 2017).…”
Section: Colour Parameters Of Freeze-dried Blackberry Powdermentioning
confidence: 99%
“…Yamashita et al. () microencapsulated anthocyanins from blackberry by‐products in maltodextrins using freeze‐drying techniques and concluded that dextrose equivalent is an important factor in anthocyanin retention, powder hygroscopicity, moisture content, acidity, water activity, and color.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Rabelo et al (2018) produced stable W/O nanoemulsions for protecting açaí berry anthocyanins and suggested the application of the products obtained in foods and pharmaceuticals. Yamashita et al (2017) microencapsulated anthocyanins from blackberry by-products in maltodextrins using freeze-drying techniques and concluded that dextrose equivalent is an important factor in anthocyanin retention, powder hygroscopicity, moisture content, acidity, water activity, and color.…”
Section: Introductionmentioning
confidence: 99%